PLACE NAMES IN THE PHRASEOLOGY OF BALTIC LANGUAGES: INTERNATIONAL, NATIONAL AND LOCAL CULTURAL SIGNS - Kļavinska, Antra (Via Latgalica, 2016)
Contemporary researchers of proper nouns are increasingly paying attention to onym semantics in both theoretical discussions and practical research. Proper nouns, in the same way as foreign language components, are associated with various extralinguistic factors, and it is for this reason that they have been analyzed in culturohistorical, social, and cross-cultural communicative contexts. In addition, research has been conducted in many languages on proper nouns as phraseological structural elements, usually emphasizing the large number and importance of anthroponyms in phraseology.Place names as phraseological unit components of semantics in Latvian and Lithuanian are analyzed in this article using the linguoculturological approach. Latvian and Lithuanian phraseological dictionaries are used in the study as primary source, with a catalogue of Latvian and Lithuanian proverbs utilized as a secondary source, providing a wider insight into phraseology.A catalogue of Lithuanian-Latvian-Lithuanian parallel texts, in addition to online sources, was used to clarify the functionalities of idiomatic expressions.Contemporary texts are dominated by toponymic phraseologisms, in addition to national cultural signs, while phraseologisms with place names of local interest are used relatively rarely in a given area. Today, discerning the meaning of less current phraseologisms is difficult or impossible; without knowing the motivation of the phraseologisms, their semantics are unclear.